Knowledge, awareness and perception of human papillomavirus testing among staff in a public university in Malaysia / Amanda C Yun-Vern ... [et al.] - Yun-Vern, Amanda C; Mazlan, Nor F; Nizaruddin, Muhammad H; Dasrilsyah, Rima A; Basri, Nurul I (Faculty of Medicine, 2024)
Introduction: HPV testing has been introduced in Malaysia for nearly 10 years. However, the Malaysian population are largely unaware of its availability and significance in the prevention of cervical cancer. Due to this fact, this study aims to determine the knowledge, awareness and perception of HPV testing and association with sociodemographic characteristics among a university staff, a study sample derived from the community in the state of Selangor, Malaysia. Methods: A cross-sectional study was conducted among University Putra Malaysia (UPM) staff from various faculties. Recruitment of study subjects was done through convenient sampling. Data on knowledge, awareness, and perception of HPV testing, alongside with socio-demographic factors were collected using online questionnaires. Statistical analyses were performed using IBM Statistical Package for Social Science (SPSS) version 26.0. Results: A total of 166 respondents participated in the study. Gender (female) and ethnicity (Chinese) were associated with higher level of knowledge on HPV testing. Meanwhile, females outperformed males in terms of awareness of the test. Other sociodemographic characteristics have no significant association with perception of HPV testing. Conclusion: This study indicated that the level of knowledge on HPV testing was generally poor, especially among Malays and other minority races. Awareness was also lower mostly among male respondents. Our findings highlighted the importance of improving the level of awareness and knowledge of HPV testing, to reduce the prevalence of HPV-related morbidity and mortality in Malaysia.